2008
DOI: 10.1109/pvsc.2008.4922856
|View full text |Cite
|
Sign up to set email alerts
|

Advanced solar cell and array technology for NASA deep space missions

Abstract: A recent study by the NASA Glenn Research Center assessed the fe A recent study by the NASA Glenn Research Center assessed the feasibility of using asibility of using photovoltaics photovoltaics (PV) to power spacecraft for outer planetary, deep space missio (PV) to power spacecraft for outer planetary, deep space missions. ns. While the majority of spacecraft have relied on While the majority of spacecraft have relied on photovoltaics photovoltaics for primary power, the for primary power, the drastic reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…[33] With the concurrent reduction of power requirements by the transition from vacuum tube to solid-state electronics and available space in launch vehicles beneath that required for deployable radiators of nuclear reactors, photovoltaic generators became the prime power source in space [10] [16], relegating all the others to niche applications mainly in exploration science missions. [11] [12] [13] [14] [15] [16] [34] [35] [36] At first confined to the region of the terrestrial planets, the feasibility photovoltaic power has meanwhile been proven out to Jupiter [37] and beyond [38] [39], and photovoltaic spacecraft are considered in studies reaching as far out as Uranus [40].…”
Section: A Brief History Of…mentioning
confidence: 99%
“…[33] With the concurrent reduction of power requirements by the transition from vacuum tube to solid-state electronics and available space in launch vehicles beneath that required for deployable radiators of nuclear reactors, photovoltaic generators became the prime power source in space [10] [16], relegating all the others to niche applications mainly in exploration science missions. [11] [12] [13] [14] [15] [16] [34] [35] [36] At first confined to the region of the terrestrial planets, the feasibility photovoltaic power has meanwhile been proven out to Jupiter [37] and beyond [38] [39], and photovoltaic spacecraft are considered in studies reaching as far out as Uranus [40].…”
Section: A Brief History Of…mentioning
confidence: 99%
“…In addition to developing lighter, higher efficiency solar cells for the arrays [21], radiation hardness of advanced IMM cell technology must be improved, in order to allow operation without degradation on orbits spiraling through the Earth's 978-1-4799-7944-8/15/$31.00 ©2015 IEEE Van Allen belts. A trade-off is to use solar concentration, allowing more shielding on the cells without added weight, but the requirements for stringent sun-pointing may make concentration approaches impractical.…”
Section: Technology Development and Maturationmentioning
confidence: 99%
“…Power for missions to Jupiter and beyond presents a challenging goal for photovoltaic power systems [1,2], but NASA missions including the Dawn mission to the asteroid belt and the Juno mission to Jupiter (Figure 1) have shown that it is possible to operate solar arrays beyond Mars, and even at Jupiter, nearly 800 million kilometers from the sun.…”
Section: Introductionmentioning
confidence: 99%